Teks Pragusa Parwa: Analisis Struktur dan Semiotik - Satriya Wibawa, I Dewa Putu; Wijana, I Made; Sukartha, I Nyoman (Humanis, 2017)
This study entitled The Pragusa Parwa Text: Structure and Semiotics Analysis. The aim of this study is to study the structure and meaning contained in Pragusa Parwa. The theory used is semiotic theory and assisted with the structural theory. Semiotic theory used is semiotic theory developed by Riffaterre. The theory which is used for structure analysis is proposed by Teeuw. In this study, there are used several methods to facilitate research. The methods used are: (1) phase of the provision of data using the method of reading the manuscript as an object of study. While the technique used is the technique of translation, (2) the data analysis stage using methods of critical analysis and hermeneutic methods that are supported by descriptive analytical techniques, (3) the stage of presentation of the results of data analysis using informal and formal methods that used sentences and words in Indonesian language. The results of this study are unfolding structures that build Pragusa Parwa text, the content and meaning contained in the text. Intrinsic structure which are build Pragusa Parwa text includes plot, setting, characterization, style, theme and message that shows the unity of the whole. Meanings in Parwa Pragusa proceeded through the matrix and model, therefore the text can obtain a sense that the ability of the primacy of science ( kottaman ??stra ) and power as a result of the ability (kawibhawan).
Keywords: Pragusa, Parwa, Semiotic